Clinical Effect of Endoscopic Pneumatic Dilation for Achalasia. Issue 28 (July 2015) - Cheng, Peng; Shi, Hai; Zhang, Yanjie; Zhou, Huabang; Dong, Jinhua; Cai, Yiting; Hu, Xing; Dai, Qiang; Yang, Wenyan; Lim., Yean
<x xml:space="preserve">Abstract</x> Abstract Although pneumatic dilation is an accepted method for the treatment of achalasia, this therapy has high recurrence and complication rates, and prolonged follow-up studies on the parameters associated with various outcomes are rare. In this prospective 10-year follow-up study, a satisfactory therapeutic effect was achieved without serious complications. We report the therapeutic experience with pneumatic dilation, having aimed to evaluate the long-term clinical safety and efficacy of pneumatic dilation. In total, 35 consecutive patients with idiopathic achalasia who underwent pneumatic dilation were followed up at regular intervals in person or by a phone interview over a 10-year period. The mean duration of the follow-up was 43.03 ± 26.34 months (range 6–120 months). Remission was assessed by the dysphagia classification and symptom scores. Patients' clinical symptom scores were calculated before and at 6 to 36 months, 37 to 60 months, and >60 months after therapy. The influence of the patients' age, gender, and disease duration on the therapeutic effect was analyzed. The success rate of the operation was 97.2% (35/36), without massive hemorrhaging, perforation or other serious complications. Dysphagia after the therapy was significantly eased (P < 0.01). In total, 35 patients have been followed up for 6 to 36 months after therapy, 21 cases for 37 to 60 months, and 5 cases for >60 months, and the patients' symptom scores separately decreased significantly compared with the pretherapy scores (P < 0.01). For these patients, the 6 to 36 months remission rate was 85.7% (30/35), the 37 to 60 months rate was 61.9% (13/21), and the >60 months rate was 40% (2/5). The dilation effect had no relationship to the patient's age, gender, and disease duration (P > 0.05). The patients in 30 cases (85.7%) were successfully treated with a single dilation, in 4 cases (11.4%) with 2 dilations, and in 1 case (2.9%) with 3 dilations. These results suggest that endoscopic pneumatic dilation is an achalasia therapy with a good response; it is a simple and safe procedure with long-term clinical effectiveness. It is a preferred method in the treatment of achalasia.